Construction of Criminal Conspiracy in Corruption Crime - Mery Rohana Lisbeth S; Elfrida Ratnawati Gultom; Jamin Ginting (Al-Makki Publisher, 2025)
The regulation of criminal conspiracy in corruption crimes in Indonesia, especially under Article 15 of the Corruption Eradication Law, raises various fundamental issues that have the potential to disrupt the principle of justice in law enforcement. This research aims to identify and analyze problems in the regulation of criminal conspiracy and provide recommendations for improvements that are fairer and in accordance with legal principles. The method used is normative research with a legal approach and qualitative descriptive analysis. Data was collected from primary, secondary, and tertiary legal sources to provide a comprehensive overview of the issues studied. The study found that the definition of criminal conspiracy in the GCPL is unclear, the sanctions are disproportionate, and the merging of the provisions with attempt and aiding and abetting has resulted in difficulties of proof. Recommendations include the need for a clear definition, separation of rules based on the nature of the act, application of the principle of proportionality in sanctions, and rewards for perpetrators who disclose conspiracies. With the proposed reforms, the law on criminal conspiracy should better reflect the principles of justice, provide legal certainty and support efforts to fight corruption effectively and humanely.